Legal Vacuum in Inheritance Dispute Resolution: A Comparative Study of Customary Law and Positive Law in Bonokeling - Zaenudin, Zaenudin; Listyani, Ajeng Aditya; Sasono, Wasis Singgih; Haryadi, Nanda Rahayu; Natasaputri, Pritha Arintha (Journal of Law, Politic and Humanities, 2025)
This study examines the legal vacuum in resolving inheritance disputes in the Bonokeling indigenous community in Pekuncen Village, Jatilawang District, Banyumas Regency, Central Java, by examining the tension between customary law norms and the national legal system. Although the customary inheritance norms of the Bonokeling indigenous community, based on family deliberation, are still alive and well, the resulting agreements often lack legal force in the state's judicial system. This study employed a normative and empirical juridical approach (socio-legal research). Data were obtained through literature review, interviews, and observations within the Bonokeling indigenous community. The findings indicate that the legal vacuum is institutional and regulatory, rather than normative, because customary norms persist but have not received adequate formal recognition. The absence of a legal mechanism to validate the results of family deliberations creates the potential for legal conflict when disputes are brought to court. Therefore, this study recommends the need for a legal strengthening scheme for customary decisions, for example through the creation of a peace deed or legal recognition of customary deliberation mechanisms. The implications of this research emphasize the importance of integrating legal pluralism into the national legal system to ensure substantive justice and legal certainty for indigenous peoples.